France : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for France. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights that the economic recovery is picking up in France, with real GDP growth projected to reach 1.6 percent in 2017 and 1.8 percent in 2018. Growth is primarily driven by buoyant corporate investment, a rebound in residential construction, and solid consumer demand. Net exports, by contrast, have been a drag on growth, and France's external position is assessed to be weaker than implied by economic fundamentals. Private sector job creation has begun to accelerate moderately and the unemployment rate has begun to recede moderately from its 10 percent post-crisis mark. Medium-term prospects will critically depend on the implementation of the reform agenda.